PENERAPAN PENDEKATAN SCIENTIFIC DENGAN MEDIA SOFTWARE PREZI UNTUK MENINGKATKAN HASIL BELAJAR MATA PELAJARAN ADMINISTRASI KEPEGAWAIAN PADA SISWA KELAS XI AP SMK NEGERI 3 SURAKARTA TAHUN AJARAN 2014/2015 - Arif Wahyu Wirawan; Patni Ninghardjanti; Jumiyanto Widodo (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2016)
The objectives of this study are: (1) to find out theimprovement of students learning outcomes in subjects staffadministration subject using Prezi software media at the XI AP classgrader of SMKN 3 Surakarta in the academic year of 2014/2015, (2)to describe problems and solutions in the implementation of scientificapproach using Prezi software media in improving learning outcomesof staff administration subject at the XI AP class grader of SMKN 3Surakarta in the academic year of 2014/2015. This research iscollaborative Classroom Action Research (CAR) conducted in twocycles, consisting of planning, implementation, observation, andreflection with two meetings in each cycle. The subjects were the XIAP class grader of SMKN 3 Surakarta, totaling 29 students andconsisting of 29 female students. Based on research that has beenconducted, it can be concluded that there is an increase in learningoutcomes of staff administration subject through the application ofscientific approach using Prezi software media. It was showed bypercentage of learning completeness result of staff administrationsubject with minimum grade criteria more than 75 in the first cycle of79.3% or 23 students and in the second cycle of 100% or 29 students.Problems occurred in the application of scientific approach usingPrezi software media, namely (a) teachers were lack of mastering theclass, (b) the division of time was not optimum, and (c) teachers wereless responsive to students who are inactive. Solution for thoseproblems are: (a) teachers are given guidance and motivation in theimplementation of scientific approach using Prezi Software media, (b)teachers should manage time effectively, and (c) teachers should bemore responsive to the students who have not been active in learning.